Monsoon Postcards : Indian Ocean Journeys - Mould, David H. (Ohio University Press, 2019)
In Monsoon Postcards, David H. Mould traverses the Indian Ocean from Madagascar through India and Bangladesh to Indonesia. He offers witty and insightful glimpses into countries linked by history, trade, migration, religion, and a colonial legacy, exploring how they confront an array of contemporary challenges.